Action Research: Pembuatan Video Promosi Tiktok Untuk Mengoptimalkan Penjualan UMKM Kedai Kopi Lapan Cuan - Hutama, Genta Arya; Rizal, Mohammad; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Promotional videos are an important thing for a company or MSME. With a good and interesting promotional video, the public can easily get information from the company or MSME. Based on the observation, Lapan Cuan Coffee Shop uses Instagram as a promotional media. However, the media used still does not contain detailed information related to the promotion of the coffee shop. This research aims to provide solutions to the problems found in the company by creating promotional videos, which will be uploaded to the TikTok application. This research is an action research (action research) involving 36 units of analysis or informants. The data collection methods used are observation, interviews, questionnaires and documentation. For data analysis, EPIC rate was used as a measure of video effectiveness. The results of the EPIC Rate analysis show that the scale range in the Empathy dimension is 4.66, in the Persuasion dimension is 4.65, in the Impact dimension is 4.6, and in the Communication dimension is 4.7. With an average EPIC rate range scale of 4.63, which means very effective. The results of this study can be concluded that making promotional videos as a media to increase sales at Lapan Cuan Coffee Shop is very effective, so that people can learn more about the coffee shop and have a positive impact on Lapan Cuan Coffee Shop. Keywords : Video; Promotion; Tiktok; Lapan Cuan Coffee Shop